The masonry timber framed load bearing structure of the Palazzo Vescovile in Mileto (Italy) - Ruggieri, N.; Geremia, F.; Pagano, E.; Salerno, G.; Stellacci, S.; Zampilli, M. (Historical earthquake-resistant timber framing in the Mediterranean area. Lecture Notes in Civil Engineering, 2016)
The Palazzo Vescovile in Mileto (Southern Italy), erected shortly after the catastrophic earthquake that struck the Calabria region, emblematically represents the application of principles and technical indications recommended in the Borbone seismic code Istruzioni and included in treatises of Eighteenth century seismic engineering. The building, characterised by various constructive events that caused a construction completion delay, presents devices aimed at consciously mitigating its seismic vulnerability, including the building geometry (i.e. in plan bi-axial symmetry, a front elevation regular development and a height limited to only one storey) as well as constructive solutions regarding the nature and the organisation of materials and resistant elements forming the load bearing structure. The vertical structural system is represented by masonry reinforced with timber frames whose main function is to bond the building intersecting walls with the aim of obtaining a box behaviour of the Palazzo Vescovile under earthquake excitations. On that purpose the particular arrangement and morphology of the members nodes, often with the addition of metallic devices, contributes to transfer stresses to a three-dimensional system of orthogonal walls. In addition to the vertical load bearing system the inter-storey floor also has a key role in influencing the building seismic response. In fact, the presence of notches strengthening the node beam to the wooden ring, improves, together with the latter, the resistance to out-of-plan actions. Furthermore, the floor is characterized by a moderate deformability, thanks to the narrow spacing and geometric features of the beams, useful for redistributing horizontal forces to the shear walls. The roof structure, constituted by king post trusses ensuring the absence of outward thrusts, benefits from the presence of saint Andrew’s crosses arranged orthogonally to the structural unit with the purpose of preventing the trusses from stacking under horizontal loads and, generally speaking, of ensuring a roof longitudinal stiffness. Moreover, the document devotes its attention to the behaviour of the Palazzo Vescovile in Mileto under gravitational actions, analysing the wooden frame contribution to the compression resistance of the entire constructive system.